Dimpled drill-bit to minimize thrust-force in bone drilling with in-vitro experimental validation - Naveed Ul Meiraj, Syed; Pandithevan, Ponnusamy; Prasannavenkadesan, Varatharajan; J Narayan, Roger (Machining science and technology, 2025)
Orthopedic surgery is a clinical procedure used to treat the damaged or diseased bones, joints, ligaments and tendons through milling, sawing, drilling and grinding operations. However, drilling through bone is the most widely used machining process that enables implant placement, fracture fixation and defect site reconstruction. In the clinical procedure, the bone screws are first guided through the ovoid holes of the compression plate and tightened through the bone using pre-drilled holes. Excessive thrust force produced during drilling into bone results in micro-cracks and bone fragmentation, which loosens the implant soon after fixation. As such, control over the thrust-force is required to avoid post-surgical complications. This study intended to minimize the thrust force produced while drilling into the bone by modifying the margins and flank faces of the widely used 3.20 mm diameter twist drill-bit. Finite element analysis coupled using the combination of the Johnson-Cook model and the Cowper-Symonds model was utilized for the drilling simulations. To authenticate the findings of the simulation with experiments, a 3.20 mm diameter twist drill-bit with dimples generated on the margins and flank faces was used. Results showed that the simulations conducted using manual and robotic-assisted bone drilling parameters were in excellent agreement with the experiments. The drill-bit modified using dimples on the margins and flank faces could effectively reduce the thrust force by a maximum of 12.31% compared with a normal drill-bit.